On advertisement call of the poison frog Ameerega berohoka (Dendrobatidae, Anura) from the Brazilian Cerrado - de Andrade, Felipe Silva; Haga, Isabelle Aquemi; Martins, Fabio Augusto Miguel; Giaretta, Ariovaldo Antonio (Zootaxa, 2014)
The poison frog genus Ameerega (Dendrobatidae) currently contains 32 species. They are distributed from central Brazil into western Amazonia to the lower Andean versant. In addition, three trans-Andean species have been allocated to Ameerega (Andrade et al. 2013; Frost 2014). Ameerega berohoka (Vaz-Silva & Maciel 2011) was described based on specimens from central Brazil (type-locality: Arenópolis, GO) and it is assumed to occur in parts of western and southwestern state of Goiás (Frost 2014). More recently, Andrade et al. (2013) extended its distribution to the state of Mato Grosso. Here we re-describe the advertisement call of A. berohoka, providing additional information regarding its temporal structure and spectral traits. Our observations also consist of a new distribution record for this species to the state of Mato Grosso.